Experimental assessment of a wireless communications platform for the built and natural heritage. (March 2016) - Martínez-Garrido, M.I.; Fort, R.
Highlights: Experimental measurements of communications quality for heritage scenarios. Evaluation methodology for wireless deployments requiring long-term monitoring. Signal strength, link quality, range and success rate. Preventing transmission failure and ensuring reliable monitoring. Wireless sensor networks for a preventive conservation. Abstract: Wireless sensor networks have become extremely popular in a number of fields in recent years, the cultural heritage among them. To date, however, communications quality has not been technically validated in any of the various built (churches, museums, archaeological sites) or natural (caves, lava tubes) heritage scenarios. The present study establishes methodology for assessing the quality of wireless communications and validating the network used, both of which are essential to guaranteeing accurate long-term monitoring in heritage scenarios. Parameters such as signal strength, link quality, range and success rate were analysed with a view to preventing transmission failure and ensuring reliable monitoring for the preventive conservation of the cultural heritage.